The Nuclear-Localized RxLR Effector PvAvh74 From Plasmopara viticola Induces Cell Death and Immunity Responses in Nicotiana benthamiana - Yin, Xiao; Shang, Boxing; Dou, Mengru; Liu, Ruiqi; Chen, Tingting; Xiang, Gaoqing; Li, Yanzhuo; Liu, Guotian; Xu, Yan (Frontiers in Microbiology, 2019)
Downy mildew is one of the most serious diseases of grapevine (Vitis spp.). The causal agent of grapevine downy mildew, Plasmopara viticola, is an obligate biotrophic oomycete. Although oomycete pathogens such as P. viticola are known to secrete RxLR effectors to manipulate host immunity, there have been few studies of the associated mechanisms by which these may act. Here, we show that a candidate P. viticola RxLR effector, PvAvh74, induces cell death in Nicotiana benthamiana leaves. Using agroinfiltration, we found that nuclear localization, two putative N-glycosylation sites, and 427 amino acids of the PvAVH74 carboxyl terminus were necessary for cell death-inducing activity. Using virus-induced gene silencing (VIGS), we found that PvAvh74-induced cell death in N. benthamiana requires EDS1, NDR1, SGT1, RAR1 and HSP90, but not BAK1. The MAPK cascade components MEK2, WIPK and SIPK were also involved in PvAvh74-induced cell death in N. benthamiana. Transient expression of PvAvh74 could suppress Phytophthora capsici colonization of N. benthamiana, which suggests that PvAvh74 elicits plant immune responses. Suppression of P. capsici colonization also was dependent on nuclear localization of PvAvh74. Additionally, PvAvh74-triggered cell death could be suppressed by another effector, PvAvh8, from the same isolate. This work provides a framework to further investigate the interactions of PvAvh74 and other RxLR effectors with host immunity.